The Utilisation of Islamic Integrated Science Comics to Teach Primary School Students about Reuse and Recycling - Alisa Asli; Roslinawati Roslan; Masitah Shahrill; Auwal Halabi Kabara (Yayasan Keluarga Guru Mandiri, 2024)
Despite implementing innovative instructional techniques, many students struggle to understand science topics. This mixed-method and action research study explored the effectiveness of Islamic integrated science comics in enhancing students' comprehension and performance on the topic of 'reuse and recycle,' a challenging area for most students. The study involved 50 Year 3 Bruneian primary school students and used quantitative and qualitative data collection methods. A Wilcoxon signed-rank test revealed significant improvements in students' post-test scores compared to their pre-test scores, demonstrating the intervention's success. Interviews with students further supported these findings, as they described the comic-based lessons as enjoyable and collaborative. The results suggest that integrating Islamic themes into science comics significantly improves students' understanding and application of scientific knowledge. This approach makes learning more engaging and aligns with students' cultural and religious contexts, thereby providing a more holistic educational experience. The study's findings have important implications for educators seeking to enhance science education in similar contexts.